Oesophageal Cancer: A Brief Overview of the Disease and a Case Study in the South African Context - Bulbulia, Bashir Ahmed; Variava, A (British Journal of Healthcare and Medical Research, 2024)
Oesophageal cancer (OC) is a worldwide disease with a high mortality. It is often diagnosed at a late stage of the illness. The sub type OC squamous cell carcinoma (OSCC) is prevalent in South Africa (SA) and endemic in some regions. Treatment is largely palliative and is a combination of surgery, chemotherapy and chemo-radiotherapy. Common complications of (OC) include dysphagia, bleeding and obstruction. Early intervention and symptomatic relief improve health related quality of life (HRQoL), however long-term survival remains dismally poor.